Contemplation of the Body - Ivan Platovnjak (Polonia Sacra)
In the tradition of Christian contemplation, we find much encouragement to both contemplate nature and how we can discover God the Creator through it and how His love is imprinted on it. St Ignatius, however, in his Contemplation for the Achievement of Love, invites the praying person to contemplate not only creation, but also himself and his body. Since there is little research or literature on contemplation of the body, the author pays special attention to it in this article. He argues that the Triune God wants to reveal Himself to every man, not only through the book of nature and the Bible, but also through his body, and that contemplation of his body can be of great help to him in this. In the first chapter he briefly defines the meaning of contemplation and then turns to an understanding of the human body in the light of Scripture and spiritual theology. In the last part, he gives various examples of how we can contemplate the body and its various parts to allow the active presence and love of the Triune God to be revealed to us.